Buildings for Education A Multidisciplinary Overview of The Design of School Buildings - Della Torre, Stefano; Bocciarelli, Massimiliano; Daglio, Laura; Neri, Raffaella (Research for Development, 2020)
This open access book presents theoretical and practical research relating to the vast, publicly financed program for the construction of new schools and the reorganization of existing educational buildings in Italy. This transformative process aims to give old buildings a fresh identity, to ensure that facilities are compliant with the new educational and teaching models, and to improve both energy efficiency and structural safety with respect to seismic activity. The book is divided into three sections, the first of which focuses on the social role of the school as a civic building that can serve the needs of the community. Innovations in both design and construction processes are then analyzed, paying special attention to the Building Information Modeling (BIM) strategy as a tool for the integration of different disciplines. The final section is devoted to the built heritage and tools, technologies, and approaches for the upgrading of existing buildings so that they meet the new regulations on building performance. The book will be of interest to all who wish to learn about the latest insights into the challenges posed by, and the opportunities afforded by, a comprehensive school building and renovation program.